Effect of fluoride-releasing adhesive systems on the mechanical properties of eroded dentin - Guedes, Ana Paula Albuquerque (2016)
The aim of the study was to evaluate the effect of erosive pH cycling with solutions that simulate dental erosion on Martens hardness (HMV) and elastic modulus (Eit) of dentin restored with fluoride-releasing adhesive systems. Twenty-seven bovine dentin slabs were restored with three adhesive systems: Adper Single Bond 2 total-etch adhesive system, One Up Bond F and Clearfil SE Protect fluoride-containing self-etching adhesive systems. The restorations were made with Filtek Z250. The HMV and Eit values at distances of 10, 30, 50 and 70 μm from the interface were evaluated using a dynamic ultra microhardness tester before and after immersion in deionized water, citric acid and hydrochloric acid (n=9). Data were submitted to repeated-measures ANOVA and Fisher's PLSD tests (□=0.05). After erosive cycling, HMV values of dentin decreased in all groups. For dentin restored with Adper Single Bond 2, the lowest values were found closer to the hybrid layer, while for One Up Bond F and Clearfil SE Protect, the values remained unaltered at all distances. For dentin restored with fluoride-releasing adhesive systems, a decrease in Eit was found, but after 30 μm this difference was not significant. The acid substances were able to alter HMV and Eit of the underlying dentin. For fluoride-releasing adhesives, the greater the distance from bonded interface, the lower the Eit values. The fluoride in One Up Bond F and Clearfil SE Protect was able to protect the underlying dentin closer to the materials. In this way, the fluoride from adhesive systems could have some positive effect in the early stages of erosive lesions.